Peningkatan Kemampuan Operasi Hitung Dasar Siswa Sekolah Dasar melalui Program Bimbingan Belajar Matematika pada Kegiatan Kuliah Kerja Nyata di Desa Toya - Mukarromatul Isnaini; Huswatun Hasanah; Baiq Ratna; Nurhazlina; Zaotul Wardi; Ahmad Rasidi (JURPIKAT, 2026)
Basic arithmetic skills are an essential competency that elementary school students must master as the foundation for learning mathematics. Observations in the village of Toya show that some students still struggle with determining the order of operations and performing multi-digit addition. This community service activity aims to improve students’ basic arithmetic skills through a Mathematics Tutoring Program as part of the Community Service Program (KKN). The program was conducted from May 7 to June 26, 2026, three times per week. Instruction utilized the Contextual Teaching and Learning (CTL) approach combined with game-based learning through Math Domino Cards. Improvements in students’ skills were analyzed using Normalized Gain (N-Gain) based on pretest and posttest results. The results showed that students’ average scores increased from 63.0 to 87.5 with an N-Gain score of 0.609, which falls into the moderate category. These results indicate that the tutoring program was effective in improving the basic arithmetic skills of elementary school students in Toya Village.